2009
DOI: 10.1364/ol.34.002222
|View full text |Cite
|
Sign up to set email alerts
|

Monoview/dual-view switchable liquid crystal display

Abstract: We present an optical device capable of displaying in two distinct viewing modes, i.e., monoview and dual-view modes. The monoview mode has a joint viewing cone and allows only the same image or video content to be displayed. The dual-view mode splits one viewing cone into two so that two different pieces of information can be displayed simultaneously in the left and the right viewing directions from the screen. Each viewing mode can be mutually switched through the modulation of the birefringence of liquid cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…In 2009, Chen et al demonstrated a DV LCD using the spatial-multiplexing approach. [13] Their design entailed low costs because of incurred savings in the additional optical elements. However, the two-step rubbing and the shadow mask treatments complicated the fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Chen et al demonstrated a DV LCD using the spatial-multiplexing approach. [13] Their design entailed low costs because of incurred savings in the additional optical elements. However, the two-step rubbing and the shadow mask treatments complicated the fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple view display, which presents multiple images to multiple observers on one screen, has gained more and more attention [1]. Observers can see different images from different viewing directions on the multiple view display.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the glasses-type 3D [3], it is inherently autostereoscopic as it allows the viewer to perceive the light as it would be scattered by the real object itself without any special eye wear. However, 67 years after its birth in 1947 [4]-almost 20 years older than liqud crystal display (LCD) [5]-holography is still a technology staying in the lab rather than going places in the commercial display markets. One reason, among others that could explain the above situation, is that in traditional holography, dichromated gelatin and silver halide are used as recording media [6], and those materials are incapable of updating holograms, thereby limiting their application merely to the optical storage of still pictures.…”
Section: Introductionmentioning
confidence: 99%